2003
DOI: 10.1124/mol.64.2.482
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Human Soluble Epoxide Hydrolase

Abstract: Human soluble epoxide hydrolase (hsEH) metabolizes a variety of epoxides to the corresponding vicinal diols. Arachidonic and linoleic acid epoxides are thought to be endogenous substrates for hsEH. Enzyme activity in humans shows high interindividual variation (e.g., 500-fold in liver) suggesting the existence of regulatory and/or structural gene polymorphisms. We resequenced each of the 19 exons of the hsEH gene (EPHX2) from 72 persons representing black, Asian, and white populations. A variety of polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
2
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(153 citation statements)
references
References 30 publications
8
138
2
4
Order By: Relevance
“…There is little known about the importance of this endogenous system within the heart even though the heart contains significant levels of functionally active CYP. Finally, and most importantly, recent human epidemiological evidence has identified associations between CYP2J2 polymorphisms and CAD, and EPHX2 polymorphisms and CHD [43,45,46,84]. These findings provide strong evidence supporting the notion that EETs play an important role in postischemic functional recovery and perhaps infarct size reduction [31,33,36,83].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…There is little known about the importance of this endogenous system within the heart even though the heart contains significant levels of functionally active CYP. Finally, and most importantly, recent human epidemiological evidence has identified associations between CYP2J2 polymorphisms and CAD, and EPHX2 polymorphisms and CHD [43,45,46,84]. These findings provide strong evidence supporting the notion that EETs play an important role in postischemic functional recovery and perhaps infarct size reduction [31,33,36,83].…”
Section: Resultssupporting
confidence: 61%
“…These studies highlight the complexity of the CYP enzyme system, emphasize the role of different CYP metabolites in cardioprotection and suggest caution in the interpretation of results when using non-selective CYP inhibitors. Recent epidemiologic data suggests an association between single nucleotide polymorphisms in the genes encoding CYP2J2, CYP2C8, CYP2C9 and EPHX2 and cardiovascular disease risk in humans supporting the functional relevance of the CYP epoxygenase pathway in the heart [43][44][45][46][47].…”
Section: Arachidonic Acid Cyp Epoxygenases and Soluble Epoxide Hydromentioning
confidence: 93%
“…47 The fragments were then subcloned into BglII/SalI sites of pAcGFP-C1 vector (BD Bioscience) to produce green fluorescent protein (GFP) fusion constructs. When expressed in mammalian cells alone, GFP is a monomeric protein (BD Bioscience), and so does not affect dimerization of hsEH.…”
Section: Plasmid Construction and Site-directed Mutagenesismentioning
confidence: 99%
“…7 An alternative strategy that has been used to increase EETs systemically is SEH inhibition. 1 We previously showed that the SEH inhibitor 12-(3-adamantan-1-yl-ureido) dodecanoic acid (AUDA) protects against cerebral ischemia in spontaneously hypertensive stroke-prone (SHRSP) rats, an animal model of essential hypertension.…”
mentioning
confidence: 99%